Molecular characterization and lesions associated with Diomedenema diomedeae (Aproctoidea: Desmidocercidae) from grey-headed albatrosses (Thalassarche chrysostoma) on Subantarctic Marion Island. Issue 2 (August 2018) - Vanstreels, Ralph E.T.; Yabsley, Michael J.; Swanepoel, Liandrie; Stevens, Kim L.; Carpenter-Kling, Tegan; Ryan, Peter G.; Pistorius, Pierre A.
Abstract: The Prince Edward Islands are Subantarctic islands in the southwest Indian Ocean that are of global importance as seabird nesting sites, and are breeding grounds for five species of albatrosses (Procellariiformes: Diomedeidae). In March–April 2016 numerous chicks of one of these species, the grey-headed albatross ( Thalassarche chrysostoma ), were found dead at colonies on Marion Island (46°57′S 37°42′E), the larger of the two Prince Edward Islands. Affected chicks were weak, prostrated, apathetic, had drooping wings, and many eventually died while sitting on the nest. Five carcasses were necropsied, and samples were obtained for pathological and parasitological analysis. Four chicks appeared to have died from starvation, and one died due to air-sac helminthiasis, with extensive hemorrhage in the air sacs and multifocal pyogranulomatous air-sacculitis. The air sac parasites were identified as Diomedenema diomedeae (Aproctoidea: Desmidocercidae). Phylogenetic analysis of the nuclear 18S rRNA gene and mitochondrial COI gene confirmed that D. diomedeae belongs to the suborder Spirurina and showed that it is most closely related to the Diplotriaenidae (superfamily Diplotriaenoidea), a family of parasites that infect the air sacs and subcutaneous tissues of a variety of bird species. To our knowledge this is the first record of the occurrence of a nematode in the respiratory tract of an albatross and the first study to provide DNA sequences for a species of the superfamily Aproctoidea. Graphical abstract: Image 1 Highlights: We examined grey-headed albatross chicks found dead at a Subantarctic Island. Diomedenema diomedeae (Aproctoidea: Desmidocercidae) was found in one albatross. D. diomedeae infection caused severe air sacculitis. The first 18S rRNA and COI sequences for a species of Aproctoidea are provided. Phylogenetic analysis suggests Aproctoidea and Diplotriaenoidea are closely related.